2018
DOI: 10.1007/s11864-018-0565-6
|View full text |Cite
|
Sign up to set email alerts
|

Treating Diffuse Large B Cell Lymphoma in the Very Old or Frail Patients

Abstract: R-CHOP has been the standard of care for diffuse large B cell lymphoma (DLBCL), curing approximately 60% of patients for more than 2 decades. However, the optimal treatment of patients who are too frail to tolerate this regimen and/or are not candidates for anthracycline therapy continues to be debated. MInT and GELA trials established addition of rituximab to CHOP in DLBCL but excluded patients older than 80 years. Multiple regimens have been tried with varying success in the very elderly, including R-mini-CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…With the right social and medical support, we believe survival and quality of life could be improved in MCL patients with comorbidities. Examples of this include dose adjustments [which have been shown to increase tolerability among comorbid patients with other lymphoma subtypes (Eyre et al , )], potential prephase treatments in elderly patients and alternative treatment combinations (such as radio‐immunotherapy) (Kumar et al , ). Our results indicate that the groups targetable for such modified interventions are those with connective tissue disease, renal disorders, cardiovascular disease and psychiatric comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…With the right social and medical support, we believe survival and quality of life could be improved in MCL patients with comorbidities. Examples of this include dose adjustments [which have been shown to increase tolerability among comorbid patients with other lymphoma subtypes (Eyre et al , )], potential prephase treatments in elderly patients and alternative treatment combinations (such as radio‐immunotherapy) (Kumar et al , ). Our results indicate that the groups targetable for such modified interventions are those with connective tissue disease, renal disorders, cardiovascular disease and psychiatric comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11]27,28 Accordingly, the management of elderly DLBCL patients is challenging due to the disease's biological aggressiveness and to treatment-related issues, both of which leading to early fatal events and, ultimately, to a reduced survival compared to younger patients. 4,5 This study demonstrated that the cumulative incidence of early mortality for elderly DLBCL patients is not negligible and is mainly associated with non-lymphoma-related predictors and that high-risk EPI and bulky disease were independently associated with early mortality in patients treated with anthracyclines.…”
Section: Discussionmentioning
confidence: 77%
“…Diffuse large B-cell lymphoma (DLBCL) represents the most common subtype of non-Hodgkin lymphoma (NHL) and is frequently diagnosed in patients older than age 65 years 1 Despite the fact that disease outcome has significantly improved for DLBCL since the introduction of rituximab together with anthracycline-containing regimens (ACR), progression-free (PFS) and overall survival (OS) remain poor for older patients compared to younger cases. [2][3][4][5] Age >60 years was included as an adverse prognostic variable in the International Prognostic Index (IPI); its role has been confirmed in the rituximab era. 6 Thus, old age is a life-threatening concern since it likely underlies comorbidities and possibly worse fitness status, contributing to increased treatment-related toxicity and adversely influencing OS.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of rituximab to cyclophosphamide, doxorubicin, vincristine, and prednisone has dramatically improved the survival of patients with DLBCL. [30] Given the absence of CD20 expression, CD20-negative DLBCLs cannot benefit from rituximab administration and pose a therapeutic dilemma. Until now there is still no standard of care for CD20-negative DLBCL.…”
Section: Discussionmentioning
confidence: 99%